What Makes an Organization Unique? Looking Inside the Box - Ferreira, J.; Fernandes, C.; Ferreira, F. (12th ACIEK International Conference, 2021)
This study attempts to understand through empirical research how characteristics of resources and capabilities (e.g., value, rareness, imitability, and organization) contribute to sustainable competitive advantages and improved firm performance. Based on a sample of 147 small and medium-sized enterprises (SMEs), this study uses primary data and multivariate statistical techniques to analyze the effects of different resource characteristics on SMEs’ competitive advantage and performance. The results suggest that the variables of value, rareness, and imitability are related to competitive advantage. However, they have varied direct and indirect effects and thus affect the development of SME performance differently. This research contributes to filling gaps in the literature created by the scarcity of quantitative studies that have applied the resource-based view theory. The findings discussed include how this approach contributes to a greater understanding of the relationship between competitive advantage and firm performance.